TINJAUAN ATAS SISTEM INFORMASI AKUNTANSI PIUTANG PADA PT. EMPAT PILAR CEMERLANG - Dian Bagrito Gunawan, - (2018)
The Field Work Practice report has the general objective of learning more about the use of accounting information systems for repayment of accounts receivable payments in the world of work and also has the specific purpose of writing this final assignment as a graduation requirement for the Diploma III program for accounting at the National Development University " Veteran" Jakarta. In carrying out the Job Training Practice, there are many benefits, one of which is to improve and expand the capabilities possessed in the real world of work. The author chooses the place of Field Work Practices at PT. Empat Pilar Cemerlang is located at Jl. Wadas Raya No. 1A - Ruko Hasanah I, Pancoran Mas, Depok, 16436. PT. Empat Pilar Cemerlang provides interior design and construction services.During carrying out fieldwork activities, the author is placed in the Finance Department. There is a task that is done in the Field Work Practice is to make invoices, make tax invoices and receipts and recapitulate data on the purchase of goods to be sold.After carrying out the Job Training, conclusions can be drawn that can shape the mentality of students in the work world and gain experience in the world of work. So that it can be used as a provision for the author to enter the real world of work in the future.